Faktor Penentu Setting Ruang Destinasi Wisata terhadap Spending Rate Wisatawan di Pantai Baron Yogyakarta - Wastuwedha Kidung Dwi Satria; Tarcicius Yoyok Wahyu Subroto (ATRIUM: Jurnal Arsitektur, 2021)
Title: Determinant Factors of Tourism Destination Space  Setting to Tourist Spending Rate at Baron Beach Yogyakarta   Gunungkidul Regency is popular for a beach tourist destination, committed for improving tourist’s arrival. However, for the past few years, the Original Local Government (OLG) of the tourism sector decreased by 2017, 2018, and 2019. Beach tourism provides the biggest percentage of The Original Local Government Revenue compared to other tourism destinations. One of the indicators that affects revenue from the tourism sector is the tourist spending rate. Therefore, it requires significant effort to identify the determinant factors of space settings that affect spending rates in Baron Beach. The research method used is mix method with the data collection technique used Behavioral Mapping that consist of Place Centered Mapping, Person Centered Mapping, and Time Budget. The conclusion of this research is the space setting of the Baron beach tourist destination is determined by 2 aspects of space and time. (a) The aspect of space is divided into 3 categories. They are high, medium, and low. (b) The aspect of time is divided into 3 categories. They are long, medium, and short. The determinant factors of space settings that affect spending rates in tourism destinations of Baron Beach are (a) spatial factor, (b) amenity factor (c) time factor.